A sketch of the Babylonian Exile - Lopasso, Vincenzo (Liber annuus, 2022)
The article investigates how the exiles from Judah lived in Babylon between 597 BC, the date of the first deportation, and the first repatriations that took place under Cyrus the Great (339) and his Achaemenid successors. At first they were deportees or prisoners of war, but they soon integrated with the environment and attained a good social and economic standing within the Babylonian population. This is evidenced by a large number of cuneiform tablets discovered in recent years, which shed light on this important historical period of the Jewish people. An image of the Exile emerges that is very different from the traditional one which was presented as a period of bitterness and suffering.